THE CHALLENGES OF ENGLISH TEACHERS IN REMOTE AREAS TOWARD ONLINE TEACHING DURING COVID-19 PANDEMIC - Niely Fawaidah Virgin; Imam Qalyubi; Zaitun Qamariah (PROJECT (Professional Journal of English Education), 2021)
This study aimed at investigating the challenges and  identifying the way the English teachers solve the challenges toward online teaching during Covid-19 pandemic. This study was qualitative research. Three instruments were used to collect the data, those are: open-ended questionnaire, interview and documentation. As a result, this study showed that there were eight challenges experienced by the English teachers in remote areas toward online teaching during Covid-19 pandemic, those are: (1) inadequate infrastructure; (2) student’s learning attention; (3) financial condition; (4) students readiness; (5) parent’s concern; (6) designing materials; (7) measuring student’s understanding, and (8) the instability of student’s motivation. During teaching-learning process, there were various ways in overcoming the challenges done by the English teachers, those are: (1) create an interactive media; (2) decide the most suitable online learning tool; (3) give additional time for the students; (4) provide adequate facilities for both teacher and student in remote areas. Keywords:  Challenge, Covid-19 Pandemic, English Teaching, Online Learning